Tandem isomerization/telomerization of long chain dienes - Torrente-Murciano, Laura; Nielsen, David J.; Cavell, Kingsley J.; Lapkin, Alexei A. (Frontiers in Chemistry, 2014)
The first example of a tandem reaction involving double-bond migration in combination with telomerization is reported. Homogeneous and heterogeneous Ru catalysts were employed as isomerisation catalysts, and telomerization was realized using a homogeneous Pd(0) precursor complex with a N-heterocyclic carbene (IMes) ligand. Overall conversions approaching 60 % were achieved with the best selectivity to telomerization products of 91% attained at 11 % conversion. Conversion was markedly higher in the presence of longer-chain alcohol (1-butanol) as the nucleophile (telogen).